Theban Priestly and Governmental Offices and Titles in the Libyan Period - Broekman, Gerard (Zeitschrift für ägyptische Sprache und Altertumskunde, 2011)
On the basis of biographical and genealogical information, mainly from Theban statues and funeral equipments, the author investigates the extent to which the most influential and/or frequently attested offices accumulate in the hands of certain individuals or families in Thebes during the Libyan Period. It appears that beside combinations of offices that in some way structurally belong together there are instances in which different offices that also occur separately accumulate in the hands of certain functionaries or specific families, notably the families of the Third and Fourth Prophets of Amun, some of whom occupy those offices for several generations.